2007
DOI: 10.1590/s0037-86822007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Evidência de alterações de permeabilidade vascular na dengue: quando a dosagem de albumina sérica define o quadro?

Abstract: A dengue é uma doença infecciosa, causada por um flavivirus e transmitida pelo mosquito do gênero Aedes aegypti que se tornou um grave problema de saúde pública em todo o mundo. Nos últimos 5 anos, o Brasil tem sido responsável por 70% dos casos relatados na região das Américas com significativo aumento das formas graves a partir de 2002 9 .Não há exames específicos para o diagnóstico da febre hemorrágica da dengue (FHD), que tem sido definida com base

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
2
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
3
2
0
1
Order By: Relevance
“…Other spontaneous hemorrhagic manifestations occurred with high frequency but less severity among patients with DHF and CD in our study, but severe bleeding was only observed in patients with DHF. Our findings for hemorrhage are similar to those reported previously 18,20 .…”
Section: Discussionsupporting
confidence: 93%
“…Other spontaneous hemorrhagic manifestations occurred with high frequency but less severity among patients with DHF and CD in our study, but severe bleeding was only observed in patients with DHF. Our findings for hemorrhage are similar to those reported previously 18,20 .…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in a study conducted by Rajoo Singh Chhina et al among patients of dengue viral fever and found that 30% patients had serum alkaline phosphatase levels raised than normal (17). Similar results were obtained in a study conducted by Brito et al among patients of dengue viral fever and found that 70 % patients had low total patients serum proteins and 71% of patients had shown hypoalbuminemia (16).…”
Section: Discussionsupporting
confidence: 88%
“…Low levels of serum albumin have been associated with an increased risk of death for dengue patients and among the general population of critical care patients [ 30 , 31 ]. Hypoalbuminemia is a classical marker of plasma leakage in dengue patients and can be useful as a early sign of severity [ 30 , 32 ]. Regarding leucocyte count, a recent study showed that increased leucocyte and cell band counts were associated with bacterial infection and a higher risk of death in dengue patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%